Evaluation of the infrazygomatic crest and mandibular buccal shelf in different sagittal skeletal patterns: a cone-beam computed tomography study - Seker Elif Dilara; Kaymakcioglu Elif; Sahin Serife; Kurt Gokmen (Australasian Orthodontic Journal, 2024)
To compare bone thickness, bone height, and density in the infrazygomatic crest (IZC) and the mandibular buccal shelf (MBS) associated with different sagittal skeletal patterns.